The Permanence of Socio-Economically Marginal Structures Within Urban Space: The Example of Bogotá - Czerny, Mirosława (Quaestiones Geographicae, 2011)
The subject of this paper is an analysis of marginal spatial development processes taking place in Bogotá, one of the largest cities in the Southern Hemisphere. Bogotá, the capital of Colombia, situated on a high plateau (Sabana de Bogotá) at over 2,500 metres above sea-level, has currently approximately 8 million inhabitants. In Bogotá, as in any major South American city, we find the characteristic, highly pronounced diversification of urban space in terms of quality, urban landscape features, and living conditions. Marginal areas in Bogotá, characterised by a low quality of urban space, can be divided into two types, their origin and attributes linked to the general social processes that have taken place here in the 20th century. They are distinguished as follows: (a) marginal districts on the outskirts of the city, resulting from a period of dynamic and unplanned urbanisation, from the 1970s until now; and (b) marginal districts in the centre of the city. This article aims to show the mechanisms that contribute to the formation of and changes in these two types of urban space.